The Significance and Practical Application of Mindfulness in the Daily Lives of People in Contemporary Thai Society - (Tevin), Phrawarin Kammasupho (Journal of Thammawat, 2025)
This article aims to study the Buddha’s teachings on “mindfulness” and how to apply these teachings to daily life. It begins with a study of the meaning and importance of mindfulness in Buddhism, which is a tool for controlling the mind and leading to the attainment of Dhamma. Mindfulness in Buddhism has a subtle and multi-level training style, including mindfulness related to the body, feelings, mind, and dharma, which is an important principle in the “Four Foundations of Mindfulness” that the Buddha advised practitioners to develop mindfulness in every moment of their lives in order to truly understand themselves and their surroundings. Studying the Buddha’s teachings on “mindfulness” is an exploration of important principles in Buddhism, which play an important role in training the mind and attaining Dhamma. Mindfulness in Buddhism does not just mean recollection or memorization, but is the awareness of every moment of life in terms of the body, feelings, mind, and dharma through the principle of “Four Foundations of Mindfulness”, which is the teaching that the Buddha advised practitioners to continuously practice mindfulness in order to be able to better understand and perceive the truth of life. Developing mindfulness helps reduce forgetfulness and suffering caused by ignorance, and helps practitioners to effectively control their emotions and thoughts, including the methods of practicing mindfulness that the Buddha advised, and the importance of mindfulness in creating peace in life. Mindfulness can lead to an understanding of the nature of one’s own mind and surroundings, allowing practitioners to live a balanced life. and finally escape from suffering.